Reference Equations for Maximal Respiratory Pressures in Healthy Children and Adolescents. - Barral-Fernández, Margarita; Jácome Pumar, María Amalia; Souto-Camba, Sonia; González-Doniz, Luz; Ramón Belmonte, María Antonia; Amor-Barbosa, Marta; Arbillaga-Etxarri, Ane; Mazzucco, Guillermo; Bravo Cortés, Pilar; Del Corral, Tamara; Martín-Valero, Rocío; Llorca Cerdà, Carlos; et al. (Elsevier, 2025)
Objectives: Maximal respiratory pressures are key indicators of respiratory muscle strength; however, reference equations and cut-offs to define respiratory muscle weakness are scarce in the European paediatric population. The aim was to create sex-specific reference equations for maximal inspiratory and expiratory pressures (PImax/PEmax) in a large sample of healthy children and to objectively establish cut-offs to define respiratory muscle weakness. Methods: A multicentre cross-sectional study was conducted across 14 Spanish centres. Healthy children aged 6–18 years, stratified by sex and age, were recruited. Maximal respiratory pressures were measured following standardized methodology in accordance with international guidelines. Reference equations were developed through multiple linear regression analyses. Age- and sex specific cut-offs for respiratory muscle weakness were determined using Z-scores ≥ 1.645 standard deviation (SD) below group means. Results: The final sample included 513 subjects (257 boys; 11.5 [SD3.5] years).

Reference equations are: (1) PImax: boys = −41.41 + 10.21 * age + 6.26 * body mass index (BMI) − 0.37 * age * BMI; girls = 125.96–0.34 * age − 0.41 * age2 − 5.75 * BMI + 0.63 * age * BMI; (2) PEmax: boys = 20.93 + 5.23 * age + 2.93 * BMI; girls = −12.67 + 11.98 * age − 0.39 * age2 + 2.57 * BMI. Cut-offs for respiratory muscle weakness are higher in boys and increase with age (p < .001). Depending on age, PImax cut-offs range from 46 to 85 cmH2O in boys and from 45 to 68 cmH2O in girls, while PEmax cut-offs span 54–98 cmH2O in boys and 57–85 cmH2O in girls. Conclusions: This study provides new reference equations for PImax and PEmax derived from the largest dataset of normative values in European children and adolescents. It also establishes age-specific cutoffs to define respiratory muscle weakness. These findings will facilitate the identification of respiratory muscle weakness and the selection of candidates for targeted training programmes.
Keywords: Músculos respiratorios; Pulmones - Enfermedades en niños; Respiratory function tests; Respiratory muscles; Muscle strength; Reference values; Paediatrics; Maximal respiratory pressures